The Effect of Application of Low-calorie Sugar on Chemical, Physical, and Organoleptic Characteristics of Red Dragon (Hylocereus polyrhizus) Fruit Syrup - Dinda Sukma Wibowo; Maria Marina Herawati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Syrup is a thick sugar solution with or without the addition of permitted food additives. Syrup usually uses high calorie cane sugar which can trigger obesity if it is not balanced by physical activity. This study aimed to determine the effect of low-calorie sugar application on chemical characteristics (including pH, vitamin C, reducing sugars, betacyanin), and physical characteristics (total dissolved solids) and organoleptic (including aroma, taste, color) in red dragon fruit syrup. The experiment was designed following randomized block design (RBD) with one-factor treatment, namely the concentration of sugar consisted of 5 treatments (K1: 3%, K2: 6%, K3: 9%, K4: 12%, K5: 15 %). Each treatment was repeated 5 (five) times to obtain 25 experimental units. The results showed that the application of low-calorie sugar significantly affected the syrup's chemical characteristics, namely reducing sugar. They had a significant effect on the physical characteristics of the syrup, namely the total dissolved solids. However, it did not significantly affect pH, vitamin C, and betacyanin levels. From the organoleptic test, the panelists liked red dragon fruit syrup the most, with a concentration of 15% for each organoleptic parameter, including aroma, taste, and color. Keywords:   Low-calorie sugar, Obesity, Organoleptic, Red dragon fruit, Syrup